Heating caused by a non-periodic ultrasound. Theory and calculations on pulse and stationary sources - Perelomova, A. (Archives of Acoustics, 2003)
General formulae on the heat release caused by any sound in the thermoviscous flow are derived, the well-known limit of the periodic source being traced. Some illustrations based on the claculations on pulse sound and stationary shock wave as acoustic sources are presented.